PERAN PERPUSTAKAAN DALAM MENINGKATKAN MINAT BACA SISWA DI SD NEGERI 1 MUARA TELADAN - Efrianti, Okta; Santoso, Budhi (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2024)
This study aims to determine the role of the library in enhancing students' reading interest at SD Negeri 1 Muara Teladan. The research method used is qualitative with a case study approach. The informants in this study consist of librarians, teachers, and students at SD Negeri 1 Muara Teladan. Data collection techniques were carried out through interviews, observations, and documentation. The data were analyzed to identify themes related to students' reading interest. The results show that the library plays a very important role in increasing students' reading interest by organizing several activities, such as accessible book lending, scheduled library visits, and literacy activities. However, challenges were identified, including low student interest in reading, insufficient budget for library facilities, and a lack of library staff. Facilities such as bookshelves, tables, and chairs need to be improved to support reading activities. Despite these challenges, students showed high enthusiasm for the activities organized by the library, highlighting the library's potential even with its limitations. With improvements in library facilities, increased budgets, and additional library staff, students' reading interest can continue to grow, positively impacting their academic achievements. The library at SD Negeri 1 Muara Teladan plays a crucial role in fostering students' reading interest, but optimizing facilities and more engaging activities are still necessary to achieve better outcomes.